Equity Issues in the Context of the rte Act, 2009 - MONDAL, AJIT (THE PRIMARY TEACHER, 2014)
One of the most debatable issues in the global context is to provide free, compulsory, universal elementary education to all children, irrespective of caste, creed, colour, religion and all other social stratifications across the globe. Education is a basic human right and has been recognised since the adaptation of the Universal Declaration of Human Rights (1948, UNO). Since then numerous international treaties have reaffirmed this right and supported entitlement to free, compulsory and universal elementary education for all children. The right to education was finally made a fundamental right of Indian children in the 6–14 age groups to get free and compulsory education. It was enshrined in the Indian Constitution as a Directive Principle of State Policy in the Article 45 before the 86th Amendment, 2002. It was the visualisation of the Founding Fathers of the Indian Constitution that took almost 59 years to translate into reality. The Constitution (86th) Amendment Act introduced new Article 21A – “the State shall provide free and compulsory education to all children of the age of 6–14 years, in such a manner as the state may, by law determine”. The Right of Children to Free and Compulsory Education Act, 2009, commonly known as RTE Act came in force with effect from 1st April, 2010.The enforcement of the Right to Education Act brings the country closer to achieving the objectives and mission of the EFA (Education for All) and MDGs (Millennium Development Goals), especially MDG2 on (Universal Primary Education) and MDG3 on (gender equality) by 2015 and hence is a historic step taken by the Government of India. This article intends to explore the provisions for equity issues related to gender disadvantaged and weaker sections of the society in the RTE Act, 2009.